African women"s theology and the re-imagining of community in Africa - Maseno-Ouma, Loreen (HTS teologiese studies, 2021)
African women’s theology has a commitment to the emancipation of women covering the several themes such as ecclesiology, hospitality, community, spirituality, sacrifice, ecology and missiology. African women’s theology examines African culture and demonstrates an understanding of women as a distinct group with inherent varieties within this category. Furthermore, African women’s theology incorporates experiences of African women in their perspectives while analysing women’s subordination. This article is a re-imagining of community in African theology. African theology has traditionally promoted the need to appreciate African culture and see to it that the integrity of African culture is upheld. However, in so doing, it laid an emphasis only on the positive aspects in African community and turned a blind eye to what was inherent in African community and not worthy to be reclaimed.Contribution: A closer look at African women’s theology provides a re-imagining of community as gleaned from Mercy Oduyoye and Teresia Hinga who assert that the quality of community in Africa ought to entail relationships, which promote reciprocity, mutuality, partnership and denounce hierarchies that promote power relations between men and women.